Association of Proinflammatory Diet With Frailty Onset Among Adults With and Without Depressive Symptoms: Results From the Framingham Offspring Study. Issue 2 (13th July 2022) - Millar, Courtney L; Dufour, Alyssa B; Hebert, James R; Shivappa, Nitin; Okereke, Olivia I; Kiel, Douglas P; Hannan, Marian T; Sahni, Shivani
Abstract: Background: Dietary inflammation is associated with increased risk of frailty. Those with depressive symptoms may be at higher risk of frailty onset because they typically have higher levels of inflammation. The study objective was to determine the association between a proinflammatory diet and frailty onset in those with and without clinically relevant depressive symptoms. Methods: This prospective study included 1 701 nonfrail individuals with self-reported baseline (1998–2001) data available for the evaluation of energy-adjusted dietary inflammatory index (E-DII TM ; calculated from food frequency questionnaires), depressive symptoms (from the Center for Epidemiologic Studies Depression; CES-D), and follow-up frailty measurements (2011–2014). Frailty was defined as fulfilling ≥3 Fried frailty criteria (i.e., slow gait, weak grip strength, unintentional weightloss, low physical activity, and self-reported exhaustion). Results are presented by baseline CES-D scores <16 or ≥16 points, which denotes the absence or presence of clinically relevant depressive symptoms, respectively. Logistic regression estimated odds ratios (OR) and 95% confidence intervals (95% CI) between E-DII and frailty onset, adjusting for confounders. Results: In all study participants, mean ( SD ) age was 58(8) years and E-DII was −1.95 (2.20; range: −6.71 to +5.40, higher scores denote a more proinflammatory diet), and 45% were male. In those without clinically relevant depressive symptoms, 1-unit higher E-DII score was associated with 14% increased odds (95% CI: 1.05–1.24) of frailty. In those with depressive symptoms, 1-unit higher E-DII score was associated with 55% increased odds of frailty (95% CI: 1.13–2.13). Conclusions: The association between inflammatory diet and increased odds of frailty appeared somewhat stronger among those with depressive symptoms. This preliminary finding warrants further investigation.